Cold chain management of vaccines a cross-sectional study of community health centers in the City of Manila - Jambaro, Mika T.​; Samonte, Sheena Jasley G.​; Sangalang, Venichel Emery D.​
The Philippines has adapted the Expanded Program on Immunization (EPI) of the World Health Organization (WHO) in local vaccination programs. However, the safety and efficacy of vaccines has yet to be prioritized through proper implementation of cold chain management. This study aimed to assess the compliance of health centers in the City of Manila to the Department of Health (DOH) guidelines on cold chain management for three components?knowledge and skills of vaccine handling personnel, basic cold chain equipment, and temperature monitoring. The study employed a descriptive cross-sectional research design. Through purposive sampling, 30 out of 59 health centers were selected. Cold chain practices were assessed through researcher-guided questionnaires, supplementary interviews and observations. The researchers used descriptive statistics (frequency) and content analysis for data processing. All respondents (n=30) were found to have health related education with only 3.33% who did not undergo the DOH-UNICEF cold chain training. There were inconsistencies in knowledge on proper storage temperatures and storage practices for vaccines available at the health centers. All health centers had basic cold chain equipment. About 96.67% could not monitor temperature twice a day, everyday due to their operating schedule. Only 6.67% of the respondents were unable to properly accomplish temperature monitoring charts due to insufficient manpower. Compliance was assessed through non-violation of any component of cold chain management. The researchers concluded that while the health centers carried out cold chain management at an extent, they were generally non-compliant to the guidelines set by the DOH.